An intentionality interpretation of meaning in mathematics education - Skovsmose, Ole [UNESP] (Springer, 2016)
The referential theory of meaning as well as the use-oriented theory of meaning have huge impacts on the discussion of meaning in mathematics education. Here, I present a third theory in terms of an intentionality interpretation of meaning, which provides an alternative departure for the discussion of meaning in mathematics education. The importance of intentionality for understanding human phenomena was emphasised by both Brentano and Husserl. They associated intentionality with a pure stream of consciousness, which constitutes an a priori to any human experience. I agree that the notion of intentionality is important; however, I find it crucial to provide a paradigmatic uprooting of this notion and to consider it as being structured by economic, political, cultural, and discursive factors. Such real-life intentionalities constitute the basis for an intentionality interpretation of meaning. I explore this interpretation with respect to mathematics education by addressing imaginations, possibilities, obstructions, hopes, fears, stereotypes and preconceptions. I relate meaning in mathematics education to far away horizons of students' life worlds, to negotiations, to political issues, to diversity and to instrumentalism.
Keywords: Intentionalities; Real-life intentionalities; Meaning in mathematics education; Intentionality interpretation of meaning; Politics of meaning